(untitled) (Statistics, Optimization & Information Computing, 2025)
This paper investigates control strategies for pulse-width modulation current source converters, which play a crucial role in integrating renewable energy sources and managing variable loads in modern power systems. A comparative study is presented between a nonlinear proportional-integral controller and two passivity-based approaches: Interconnection and Damping Assignment Passivity-Based Control and PI-PBC. The analysis aims to evaluate the dynamic response, robustness, and stability of each method under realistic operating conditions. Simulation results reveal that while PI-based controllers perform satisfactorily under steady-state or slowly varying conditions, their performance deteriorates significantly during abrupt load changes or transient disturbances. In contrast, passivity-based strategies demonstrate superior robustness, enhanced disturbance rejection, and improved system stability across a wide range of scenarios. Comprehensive simulations were conducted under variable load profiles, including step and ramp disturbances, to assess control performance using key metrics such as current tracking accuracy, total harmonic distortion, and settling time. The results provide valuable insights for designing reliable and adaptive control schemes in applications such as microgrids, electric drives, and energy conversion systems.